Analisis Yuridis Pengaturan Perizinan Apotek dalam Mencapai Kepastian Hukum - Supriadi, Yanyan; Linda, Maura; Sutrisno, Sutrisno (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study aims to analyze the reconstruction of pharmacy licensing in Indonesia based on the general principles of good governance to achieve legal certainty. The focus of the study is the implementation of the Minister of Health Regulation Number 14 of 2021 concerning Standards for Business Activities and Products in the Implementation of Risk-Based Business Licensing in the Health Sector and its impact on local regulations such as the Banjar Regent Regulation and the Decree of the Head of the Bogor Regency Health Office. This study found that although the regulation was designed to standardize pharmaceutical service standards, there were differences in interpretation and implementation at the regional level. It creates legal uncertainty for operating pharmacies, especially regarding the requirements for the number of pharmaceutical personnel, such as pharmacists and pharmaceutical technicians, in pharmacies that operate 24 hours. The method used in this study is a normative legal approach with an analysis of laws and regulations and related documents. The study results indicate that although the Minister of Health Regulation Number 14 of 2021 provides a clear legal framework, its implementation in the regions requires reconstruction to comply with the principles of good governance, such as legal certainty, openness, and justice. Alignment between central and regional regulations is vital to ensure optimal pharmaceutical service standards and reduce bureaucratic obstacles in licensing. Concrete steps to unify regulations at the central and regional levels are needed to create a more effective and efficient pharmacy licensing system.